RNA sequencing profiling of mRNAs, long noncoding RNAs, and circular RNAs in Trigeminal Ganglion following Temporomandibular Joint inflammation - Liu, Xiaojun; Zhao, Chenchen; Han, Yupeng; Feng, Ruixia; Cui, Xiaona; Zhou, Yaoyao; Li, Zhisong; Bai, Qian (Frontiers in Cell and Developmental Biology, 2022)
Patients with temporomandibular joint disorders (TMD) have high levels of inflammatory pain-related disability, which seriously affects their physical and mental health. However, an effective treatment is yet to be developed. Both circular RNAs (circRNAs) and long noncoding RNAs (lncRNAs) contribute to regulating pain conduction. In our current study, we report the expression profiles of circRNAs, lncRNAs, and mRNAs in the trigeminal ganglion (TG) associated with complete Freund’s adjuvant (CFA)-induced TMD inflammation pain. The collected TGs from the experimental (CFA) and control (saline) groups were processed for deep RNA sequencing. Overall, 1078,909,068 clean reads were obtained. A total of 15,657 novel lncRNAs were identified, where 281 lncRNAs were differentially expressed on CFA3D and 350 lncRNAs were differentially expressed on CFA6D. In addition, a total of 55,441 mRNAs and 27,805 circRNAs were identified, where 3,914 mRNAs and 91 circRNAs were found differentially expressed, between the CFA3D and saline groups, while 4,232 mRNAs and 98 DE circRNAs were differentially expressed between the CFA6D and saline groups. Based on functional analyses, we found that the most significant enriched biological processes of the upregulated mRNAs were involved in the immunity, neuron projection, inflammatory response, MAPK signaling pathway, Ras signaling pathway, chemokine signaling pathway, and inflammatory response in TG. Further analyses of Gene Ontology and the Kyoto Encyclopedia of Genes and Genomes pathway suggest the involvement of dysregulated genes in the pain occurrence mechanism. Our findings provide a resource for expression patterns of gene transcripts in regions related to pain. These results suggest that apoptosis and neuroinflammation are important pathogenic mechanisms underlying TMD pain. Some of the reported differentially expressed genes might be considered promising therapeutic targets. The current research study revealed the expression profiles of circRNAs, lncRNAs, and mRNAs during TMD inflammation pain and sheds light on the roles of circRNAs and lncRNAs underlying the pain pathway in the trigeminal system of TMD inflammation pain.